Antioxidant levels and activities of selected seeds of Malaysian tropical fruits - Senawi, Norshazila; Syed Osman Idid, Syed Zahir Idid; Koya, Mustapha Suleiman; Mohamed Rehan, Aisyah; Kamarudin, Kamarul Rahim (Nutrition Society of Malaysia, 2010)

(untitled)
The aims of this study are to determine and compare the antioxidant levels and activities (i.e. primary and secondary) between selected seeds of Malaysian tropical fruits - guava (Psidium guajava), mango (Mangifera indica L.) and papaya (Carica papaya L.). Seeds are among byproducts from the processing of fruitsbased products. Instead of discarding seeds as waste, seeds with high potential as antioxidants could be utilised for commercial purposes. Accordingly, the selected seeds of Malaysian tropical fruits were tested in this study for total phenolic content (TPC), free radical scavenging activity by 1, 1- diphenyl-2- picrylhydrazyl (DPPH) assay and metal ion chelating effect by ferrous ion chelating (FIC) assay. Extraction of antioxidant compounds from sample was done with 70% ethanol. TPCs of the seeds were expressed as gallic acid equivalents (GAE) in mg per 100 g fresh seed weight. TPC assay showed that mango seeds had the highest TPC (i.e. 32 ± 0.001 mg GAE) followed by guava seeds (i.e. 20 ± 0.001 mg GAE) and papaya seeds (8 ± 0.003 mg GAE). For DPPH assay, IC50 data showed that mango seed extract scavenged 50% DPPH radicals at the lowest concentration (0.11 ± 0.01 mg/mL) followed by the positive control BHA (0.13 ± 0.01 mg/mL), guava seed extract (0.26 ± 0.01 mg/mL) and papaya seed extract (0.34 ± 0.01 mg/mL). Interestingly, all seed extracts showed higher free radical scavenging activities than BHA after sample concentration of 0.60 mg/mL. However, FIC assay indicated that metal ion chelating effects of all seed extracts were weaker than BHA suggesting that the fruit seeds are not sources of good metal ion chelators. Overall, present results suggest that TPC of the seeds show strong negative correlation with their primary antioxidant activity (r= -0.985, R2= 0.970), and not all compounds in extracts which could scavenge DPPH radicals are good metal ion chelators. Mango seeds relatively showed the highest antioxidant level and primary antioxidant activity followed by guava seeds and papaya seeds.